Paradoxical reactions and biologic agents: a French cohort study of 9303 patients. (1st November 2022) - Bataille, Pauline; Layese, Richard; Claudepierre, Pascal; Paris, Nicolas; Dubiel, Julien; Amiot, Aurélien; Sbidian, Emilie; ,
Abstract: Background: Paradoxical reactions (PRs) are defined as the occurrence during biologic therapy of a pathological condition that usually responds to these drugs. Objectives: To estimate the incidence of PRs and identify risk factors. Methods: Multicentre study of the database for the Greater Paris University Hospitals, including biologic‐naive patients receiving anti‐tumour necrosis factor‐α, anti‐interleukin‐12/23, anti‐interleukin‐17 or anti‐α4β7‐integrin agents for psoriasis, inflammatory rheumatism or inflammatory bowel disease (IBD). We used natural language processing algorithms to extract data. A cohort and a case–control study nested in the cohort with controls selected by incidence density sampling was used to identify risk factors. Results: Most of the 9303 included patients (median age 43·0, 53·8% women) presented an IBD (3773, 40·6%) or a chronic inflammatory rheumatic disease (3708, 39·9%), and 8489 (91·3%) received anti‐TNF‐α agents. A total of 297 (3·2%) had a PR. The global incidence rate was 7·6 per 1000 person‐years [95% confidence interval (CI) 6·8–8·5]. The likelihood of PR was associated with IBD [adjusted odds ratio (aOR) 1·9, 95% CI 1·1–3·2, P = 0·021] and a combination of at least two inflammatory diseases (aOR 6·1, 95% CI 3·6–10·6, P < 0·001) and was reduced with conventional synthetic disease‐modifying antirheumatic drugs (csDMARDs) and corticosteroids (aOR 0·6, 95% CI 0·4–0·8, P = 0·002; and OR 0·4, 95% CI 0·2–0·6, P = 0·002, respectively). Conclusions: The likelihood of PRs was associated with IBD or a combination of a least two inflammatory diseases. More studies are needed to assess the benefit of systematically adding csDMARDs for such high‐risk patients. What is already known about this topic? Most published studies about paradoxical reactions concern paradoxical psoriasis in patients receiving anti‐tumour necrosis factor‐α agents. Few data are available for other paradoxical reactions and the most recent biologics. What does this study add? Risk of paradoxical reactions was increased with inflammatory bowel disease and a combination of at least two inflammatory diseases. Risk of paradoxical reactions was reduced with conventional synthetic disease‐modifying antirheumatic drugs or corticosteroid therapy, which could be added for high‐risk patients. Abstract: Most published studies are about paradoxical reactions related to paradoxical psoriasis in patients receiving an anti‐tumor necrosis factor‐alpha. A few data are available for the other paradoxical reactions and the most recent biologic agents.Risk of paradoxical reactions was increased with IBD or a combination of at least two inflammatory diseases and infliximab treatment and was reduced with csDMARDs or corticosteroid therapy that could be added for high‐risk patients. Linked Comment: C. Paul. Br J Dermatol 2022; 187:638 . Plain language summary available online